Manganese Oxidation by Spores and Spore Coats of a Marine Bacillus Species - de Vrind, Johannes P. M. (1986)
Bacillus sp. strain SG-1 is a marine bacterial species isolated from a near-shore manganese sediment sample. Its mature dormant spores promote the oxidation of Mn(2+) to MnO(2). By quantifying the amounts of immobilized and oxidized manganese, it was established that bound manganese was almost instantaneously oxidized. When the final oxidation of manganese by the spores was partly inhibited by NaN(3) or anaerobiosis, an equivalent decrease in manganese immobilization was observed. After formation of a certain amount of MnO(2) by the spores, the oxidation rate decreased. A maximal encrustment was observed after which no further oxidation occurred. The oxidizing activity could be recovered by reduction of the MnO(2) with hydroxylamine. Once the spores were encrusted, they could bind significant amounts of manganese, even when no oxidation occurred. Purified spore coat preparations oxidized manganese at the same rate as intact spores. During the oxidation of manganese in spore coat preparations, molecular oxygen was consumed and protons were liberated. The data indicate that a spore coat component promoted the oxidation of Mn(2+) in a biologically catalyzed process, after adsorption of the ion to incipiently formed MnO(2). Eventually, when large amounts of MnO(2) were allowed to accumulate, the active sites were masked and further oxidation was prevented.